2020
DOI: 10.4236/jcc.2020.82004
|View full text |Cite
|
Sign up to set email alerts
|

Graphical Processing Unit Based Time-Parallel Numerical Method for Ordinary Differential Equations

Abstract: On-line transient stability analysis of a power grid is crucial in determining whether the power grid will traverse to a steady state stable operating point after a disturbance. The transient stability analysis involves computing the solutions of the algebraic equations modeling the grid network and the ordinary differential equations modeling the dynamics of the electrical components like synchronous generators, exciters, governors, etc., of the grid in near real-time. In this research, we investigate the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The time domain simulations of the test systems discussed in [10] is performed using the modified PRA implementation. In figures 4a and 5a, the variation of the rotor angle for cases 1 and 2 are presented.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time domain simulations of the test systems discussed in [10] is performed using the modified PRA implementation. In figures 4a and 5a, the variation of the rotor angle for cases 1 and 2 are presented.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The results in [10] [11] showed that a significant amount of time is spent on the predictor step computing ̃ values. This step impacted the overall performance of the original PRA and showed poor scaling when implemented on many-core and multi-core architectures for a system of inter-dependent ODEs.…”
Section: ̃=mentioning
confidence: 99%